2020
DOI: 10.1152/ajpendo.00094.2020
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy modifies lipid metabolism of retroperitoneal white fat in rats: a proteomic approach

Abstract: Menopause is often accompanied by visceral obesity. With the aim of exploring the consequences of ovarian failure on visceral fat, we evaluated the effects of ovariectomy and estrogen replacement on the proteome/phosphoproteome and on the fatty acids profile of the retroperitoneal adipose depot (RAT) of rats. Eighteen three months old female Wistar rats were either ovariectomized or sham-operated and fed with standard chow for three months. A sub-group of ovariectomized rats received estradiol replacement. RAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 66 publications
(60 reference statements)
2
19
0
Order By: Relevance
“…However, in the present study, in addition to the 32.9% increase in visceral fat in OVX rats, there was also a 29.0% increase in the percentage of carcass fat (muscle) thus demonstrating a proportionality in the increase between visceral and muscle fat. This increase in body fat has been reported as being a consequence of aging in postmenopausal women, which could promote insulin resistance and an increased risk of chronic non-communicable diseases [1,2,4,5,8,11,12,16]. More importantly, the present study demonstrated that regular aerobic exercise reduced muscle fat in OVX rats to the levels of sedentary Sham rats.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, in the present study, in addition to the 32.9% increase in visceral fat in OVX rats, there was also a 29.0% increase in the percentage of carcass fat (muscle) thus demonstrating a proportionality in the increase between visceral and muscle fat. This increase in body fat has been reported as being a consequence of aging in postmenopausal women, which could promote insulin resistance and an increased risk of chronic non-communicable diseases [1,2,4,5,8,11,12,16]. More importantly, the present study demonstrated that regular aerobic exercise reduced muscle fat in OVX rats to the levels of sedentary Sham rats.…”
Section: Discussionsupporting
confidence: 67%
“…Obesity is growing worldwide, being one of the main public health problems, especially in postmenopausal women [1][2][3][4]. Menopause is a natural aging process in women that promotes metabolic and body changes by increasing weight and body fat, which may increase the risk of cardiovascular diseases, obesity, diabetes, hypertension and cancer [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…ERβ globally regulates lipid homeostasis[ 145 ], its activation in obesity increases whole body metabolism and mitochondrial biogenesis as a countermeasure to excess WAT lipid storage[ 312 ]. Oophorectomy alters WAT lipid metabolism[ 342 ], the plasma levels of E2 are affected by diet[ 284 ] and determine body fat deposition[ 343 ], probably through central (brain) control mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Menopause is an important risk factor for the development of obesity, which becomes further exacerbated when associated with the consumption of energy dense diets 33 . Our group has recently demonstrated that ovariectomy modified the fatty acid profile of RET total lipid extract, which was marginally normalized by oestrogen replacement 30 . Those results confirm that the loss of ovarian hormones, combined or not with the consumption of a lard-enriched diet, could lead to impaired lipid and fatty acid metabolism in visceral adipose tissue.…”
Section: Discussionmentioning
confidence: 98%
“…The limitation of this study was to not include triglycerides, which represents a predominant fraction of neutral lipids within adipose tissue. Our choice to exclude triglycerides was based on data from our previous study where we demonstrated that ovariectomy leads to a disruption of the fatty acid composition of total lipid extract, which includes, in its majority, the triglyceride portion of neutral lipids 30 . By choosing to focus on cholesteryl esters, monoglycerides and diglycerides we aimed to investigate the more subtle and dynamic portions of the neutral lipid synthesis pathway within the adipose tissue that would confirm any metabolic changes taking place.…”
Section: Discussionmentioning
confidence: 99%